Ethnomathematics of the religious beliefs and rituals of the Bagobo Tagabawa of Southern Mindanao, Philippines - Gabica, Dexter G. (Ethnomathematics Journal, 2026)
This study examines the ethnomathematical dimensions of the religious beliefs and ritual practices of the Bagobo Tagabawa of Southern Mindanao. Grounded in ethnographic analysis and informed by ethnomathematics theory, it investigates how mathematical ideas are embedded, enacted, and transmitted through culturally meaningful religious activities. Drawing on field observations, elder narratives, and ethnographic and ethnomedical literature, the study analyzes ritual practices such as pilgrimage to Apo Sandawa, spatial organization of ritual spaces, healing practices involving the preparation of lana, symbolic offerings, music, and dance. Findings show that these practices embody systematic mathematical concepts including geometry, measurement, ratio and proportion, sequencing, patterning, and cyclicity. Mathematical reasoning among the Tagabawa is expressed through embodied movement, spatial design, material preparation, and collective coordination, and is inseparable from cultural values of balance, reciprocity, and harmony. The study highlights the pedagogical potential of Tagabawa ethnomathematics for culturally responsive and place-based mathematics education and contributes to efforts to decolonize mathematics education by recognizing indigenous rituals as legitimate sites of mathematical knowledge.